Analysis of Digitalization Developments on Changes in Consumer Behavior - Dina, Farah (Inovbiz: Jurnal Inovasi Bisnis, 2024)
The increasingly advanced development of digital technology has become part of people's lifestyle and needs in everyday life. This has an impact on increasing the need to use internet data packages. The purpose of this research is to determine the development of increasing cellular operators in Indonesia, to analyze factors changing consumer behavior in using Internet data packages, and to determine the development of internet technology on the revenue of internet data card traders. This research uses descriptive analysis with an approach using qualitative and quantitative methods (primary data), using dependent variables, namely: cultural, social, personal and psychological. The results of research conducted by researchers state that the development of internet technology has had a big influence on increasing sales of internet data cards and package prices (HP) have a positive and significant effect on the revenue of internet package card traders with the hypothesis being accepted but with the variable number of package quotas (JKP) and length of active period (LMA) has a positive effect but is not significant, so the hypothesis is rejected..Keywords: Digital Technology, Internet, Culture, Social